San Emeterio, Gonzalo. Shimabaraki, una crónica de la rebelión de Shimabara. Madrid: AUM Ediciones, 2019 [ISBN: 978-84-8344-679-9] - Abad de los Santos, Rafael (Mirai. Estudios Japoneses, 2021)
This review presents the work Shimabaraki, a chronicle of the Shimabara rebellion (Spanish) by Professor Gonzalo San Emeterio, published by the Autonomous University of Madrid. This work constitutes the first complete translation into a Western language of the Shimabara-ki text, which narrates the last great uprising carried out by Japanese Christians in the archipelago during the Edo period. The author has divided the work into three main blocks. The first analyzes the historical context in which the rebellion occurred. The second examines the chronicle from a textual, literary, and editorial point of view. And finally, we are offered a translation of the text into modern Spanish language. This translation and the preceding analysis constitute an invaluable contribution to the understanding of Japanese history in the 17th century, not only from a socio-cultural and religious point of view but also from a literary and traductological perspective.